E0151 Expression of IL-17 in viral induced dilated cardiomyopathy mice. (17th November 2010) - Song, Lin; Weifeng, Wu
Abstract : Objective: To investigate Interleukin 17 (IL-17) levels in viral dilated cardiomyopathy (DCM) mice, aiming at effect of IL-17 in viral DCM. Methods: 40 male BABL/c mice were divided into two groups, the DCM group and the control. The DCM group mice were peritoneal injected Coxsackievirus B3 (CVB3) monthly. After 180 days, all mice were sacrificed and IL-17 mRNA of splenocytes were measured by RT-PCR. Results: In the DCM mice, the heart weight was higher, and the ventricular wall was thinner than the control, and fibrosis in hearts were observed. IL-17 mRNA of splenocytes in DCM mice could be detected and the controls' were zero (0.15±0.04 vs 0.00±0.00, p<0.01). Conclusion: We successfully built murine DCM model by monthly peritoneal injection of CVB3 for 180 days in the DCM group. In the DCM mice, the heart weight was higher, and the ventricular wall was thinner than the control, and fibrosis in heart was observed. The mRNA levels of IL-17 were promoted in Coxsackievirus induced DCM mice. This result suggested that IL 17 which secreted by Th17 subset could be detected in DCM mice, it seems that the Th17 cells might differentiated in DCM mice.